O008 Embedding digital sleep health into primary care practice: perspectives of general practitioners, nurses, and pharmacists. (7th October 2021) - Cheung, J; Menczel Schrire, Z; Aji, M; Salomon, H; Doggett, I; Glozier, N; Bartlett, D; Wong, K; Grunstein, R; Gordon, C
Abstract: Introduction: Digital health interventions (DHI) have the potential to address the unmet sleep health needs of patients in primary care. The current study explored primary care health providers' attitudes and beliefs towards DHIs for sleep health and the implementation into practice. Methods: A mixed-methods study was conducted in a convenience sample of primary care service providers (GPs, nurses, pharmacists). An online survey captured participants' scope of practice and attitudes towards DHIs. Associations between practice factors and attributes of DHIs were explored. A subset of participants was interviewed to explore perceived barriers/facilitators for implementing DHIs into primary care, which was thematically analysed using the Framework Approach. Results: 71 surveys were returned (GPs = 26, nurses = 21, pharmacists = 24) and 37 interviews were conducted (GPs = 13, nurses = 12, pharmacists = 12). Self-reported familiarity with DHIs was highest for GPs followed by pharmacists and nurses. Three major themes were identified: 1) Technology in Current Practice 2) Education Gaps and Training Needs and 3) Envisioning a Model of Care. Participants reported the "vague" definition of DHIs and mostly spoke in terms of personal experience and/or the health informatics systems used in practice. Despite recognising knowledge gaps, participants were confident in becoming upskilled and welcomed the idea of expanding digitalisation into sleep health. However, implementation success would depend on a supportive practice culture, patient uptake, and revising reimbursement structures. Conclusion: With appropriate training and support, service providers highlighted the potential for embedding DHIs into primary care to optimise sleep health.